Genome-Wide Screening of mRNA Expression in Leprosy Patients - Belone, Andrea de Faria F.; Rosa, Patrícia S.; Trombone, Ana P. F.; Fachin, Luciana R. V.; Guidella, Cássio C.; Ura, Somei; Barreto, Jaison A.; Pinilla, Mabel G.; de Carvalho, Alex F.; Carraro, Dirce M.; Soares, Fernando A.; Soares, Cleverson T. (Frontiers in Genetics, 2015)
Leprosy, an infectious disease caused by Mycobacterium leprae, affects millions of people worldwide. However, little is known regarding its molecular pathophysiological mechanisms. In this study, a comprehensive assessment of human mRNA was performed on leprosy skin lesions by using DNA chip microarrays, which included the entire spectrum of the disease along with its reactional states. Sixty-six samples from leprotic lesions (10TT, 10BT, 10BB, 10BL, 4LL, 14R1, and 10R2) and nine skin biopsies from healthy individuals were used as controls (CC) (ages ranged from 06 to 83 years, 48 were male and 29 female). The evaluation identified 1,580 differentially expressed mRNAs [Fold Change (FC)≥2.0, p<0.05] in diseased lesions versus healthy controls. Some of these genes were observed in all forms of the disease (CD2, CD27, chit1, FA2H, FAM26F, GZMB, MMP9, SLAMF7, UBD) and others were exclusive to reactional forms (Type "1" reaction: GPNMB, IL1B, MICAL2, FOXQ1; Type "2" reaction: AKR1B10, FAM180B, FOXQ1, NNMT, NR1D1, PTX3, TNFRSF25). In literature, these mRNAs have been associated with numerous pathophysiological processes and signaling pathways and are present in a large number of diseases. The role of these mRNAs maybe studied in the context of developing new diagnostic markers and therapeutic targets for leprosy.